ENGLISH-AN ANALYTICAL STUDY OF TRADITIONS OF TRIAL AND TRIBULATION IN THE LIGHT OF SIX CANONICL BOOKS - Peeral khan; Naheed Arain; Jabeen Bhutto (دی اسکالر)
The purpose of this research study is to deduce some key issues of Muslims regarding their negligence from the trial and tribulation of this world and suggests some way outs for their pleasant existence in this mundane world. Allah (S.W.T) has blessed human beings with free will in choosing good and evil, having imparted the knowledge of both spheres. It is necessary for the seeker of goodness to gain objective information about both good and evil. Some of the companions of Holy prophet collected information from him about virtue, while some about vice. They conveyed what they learned in the context of the traditions of trial and tribulation to their followers, who passed it through the stages of editing to the Muslim Community in the form of collections. This information is as important as the protection of beliefs or creeds. Since the traditions of tribulation are related to purely practical world, and have to do with human life, human dignity and human wealth. It is very important to acquire their knowledge in purview of the correct context and authentication. However, the study points out the lack of acquaintance of the authentic knowledge of the Aḥādīth by layman and sticking to whims has led to the chaos and confusion and has put Muslim community in the depth of degradation, study also recommends some remedies to avert from the situation and stick to path of guidance.